2000
DOI: 10.1053/ejvs.1999.1083
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-enhanced Magnetic Resonance Angiography, Digital Subtraction Angiography and Duplex of the Iliac Arteries Compared with Intra-arterial Pressure Gradient Measurements

Abstract: with intra-arterial pressure measurements as the reference method, similar results were achieved with Gd-MRA, DSA and duplex concerning the detection of haemodynamically significant iliac artery stenoses. The use of source images and multiplanar reconstructions resulted in higher accuracy for the detection of occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

2005
2005
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 16 publications
3
28
1
2
Order By: Relevance
“…For evaluation of each vascular region, we used three-dimensional (3-D) fast spin echo (FSE) T1-weighted sequences with the following parameters: TR= 6 ms, TE 1.5 ms, flip angle 35°, slice thickness 1.5 mm (3 mm with 1.5-mm overlap), field of view 430 mm, matrix 512×512, number of slices 70 and acquisition time 28 s. Overall acquisition time of successive sequences, including the time needed for two table moveIntroduzione L'angiografia mediante risonanza magnetica (Angio-RM) ha trovato negli ultimi anni applicazione sempre più ampia nella valutazione delle arteriopatie degli arti inferiori. I progressi tecnologici hanno fatto sì che tale indagine possa garantire una sensibilità ed una specificità elevate, utilizzando l'angiografia digitale come gold standard, pur se i lavori pubblicati riportano un range di percentuali assai ampio (sensibilità tra il 71% e il 100%, specificità tra il 63% e il 100%) [1][2][3][4][5][6][7][8][9][10][11]. Molti lavori hanno preso quindi in considerazione il suo apporto diagnostico ed hanno sottolineato i suoi benefici, per il trascurabile costo biologico.…”
Section: Examination Techniqueunclassified
See 3 more Smart Citations
“…For evaluation of each vascular region, we used three-dimensional (3-D) fast spin echo (FSE) T1-weighted sequences with the following parameters: TR= 6 ms, TE 1.5 ms, flip angle 35°, slice thickness 1.5 mm (3 mm with 1.5-mm overlap), field of view 430 mm, matrix 512×512, number of slices 70 and acquisition time 28 s. Overall acquisition time of successive sequences, including the time needed for two table moveIntroduzione L'angiografia mediante risonanza magnetica (Angio-RM) ha trovato negli ultimi anni applicazione sempre più ampia nella valutazione delle arteriopatie degli arti inferiori. I progressi tecnologici hanno fatto sì che tale indagine possa garantire una sensibilità ed una specificità elevate, utilizzando l'angiografia digitale come gold standard, pur se i lavori pubblicati riportano un range di percentuali assai ampio (sensibilità tra il 71% e il 100%, specificità tra il 63% e il 100%) [1][2][3][4][5][6][7][8][9][10][11]. Molti lavori hanno preso quindi in considerazione il suo apporto diagnostico ed hanno sottolineato i suoi benefici, per il trascurabile costo biologico.…”
Section: Examination Techniqueunclassified
“…The high diagnostic accuracy of MRA in the evaluation of lower-limb arteries is an established fact [1][2][3][4][5][6][7][8][9][10][11]. In addition, MRA no doubt offers clear advantages over angiography if biological costs are considered since it is non-invasive, involves no ionising radiation and makes use of a paramagnetic contrast agent, which is safer than organic iodinated products.…”
Section: Full Costmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons with intra-arterial pressure measurements (IAPM) have, however, shown that some hemodynamically significant stenoses will remain undetected if only morphological modalities are used (22,24). For this reason, invasive pressure measurements are still required before decisions on interventional procedures can be made, at least in borderline cases.…”
mentioning
confidence: 99%